Functional Electrical Stimulation: Cardiorespiratory Adaptations and Applications for Training in Paraplegia - Deley, Gaëlle; Denuziller, Jérémy; Babault, Nicolas (Sports medicine (Auckland), 2015)
Regular exercise can be broadly beneficial to health and quality of life in humans with spinal cord injury (SCI). However, exercises must meet certain criteria, such as the intensity and muscle mass involved, to induce significant benefits. SCI patients can have difficulty achieving these exercise requirements since the paralysed muscles cannot contribute to overall oxygen consumption. One solution is functional electrical stimulation (FES) and, more importantly, hybrid training that combines volitional arm and electrically controlled contractions of the lower limb muscles. However, it might be rather complicated for therapists to use FES because of the wide variety of protocols that can be employed, such as stimulation parameters or movements induced. Moreover, although the short-term physiological and psychological responses during different types of FES exercises have been extensively reported, there are fewer data regarding the long-term effects of FES. Therefore, the purpose of this brief review is to provide a critical appraisal and synthesis of the literature on the use of FES for exercise in paraplegic individuals. After a short introduction underlying the importance of exercise for SCI patients, the main applications and effects of FES are reviewed and discussed. Major findings reveal an increased physiological demand during FES hybrid exercises as compared with arms only exercises. In addition, when repeated within a training period, FES exercises showed beneficial effects on muscle characteristics, force output, exercise capacity, bone mineral density and cardiovascular parameters. In conclusion, there appears to be promising evidence of beneficial effects of FES training, and particularly FES hybrid training, for paraplegic individuals.